2017
DOI: 10.18632/oncotarget.22524
|View full text |Cite
|
Sign up to set email alerts
|

FAM3C activates HSF1 to suppress hepatic gluconeogenesis and attenuate hyperglycemia of type 1 diabetic mice

Abstract: FAM3C, a member of FAM3 gene family, has been shown to improve insulin resistance and hyperglycemia in obese mice. This study further determined whether FAM3C functions as a hepatokine to suppress hepatic gluconeogenesis of type 1 diabetic mice. In STZ-induced type 1 diabetic mouse liver, the FAM3C-HSF1-CaM signaling axis was repressed. Hepatic FAM3C overexpression activated HSF1-CaM-Akt pathway to repress gluconeogenic gene expression and ameliorate hyperglycemia of type 1 diabetic mice. Moreover, hepatic HSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, whether they are coordinated to promote the development of cancers remains unknown. 44 The current and our previous findings 27,28 revealed that FAM3C likely mediates TGFβ-promoted Akt activation in the pathogenesis of EMT through YY1-HSF1 signalling axis. FAM3C up-regulates YY1 to induce HSF1 expression, finally activating Akt-Cyclin D1 pathway to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, whether they are coordinated to promote the development of cancers remains unknown. 44 The current and our previous findings 27,28 revealed that FAM3C likely mediates TGFβ-promoted Akt activation in the pathogenesis of EMT through YY1-HSF1 signalling axis. FAM3C up-regulates YY1 to induce HSF1 expression, finally activating Akt-Cyclin D1 pathway to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 59%
“…27,28 However, in case of TGFβ overproduction, long-term activation of FAM3C-YY1-HSF1 pathway will trigger the development of cancers in various tissues including breast tissue by promoting excessive Akt activation. Under insulin resistance, repression of FAM3C by the factors such as fatty acids will impair YY1-HSF1-Akt pathway to enhance hepatic gluconeogenesis and lipogenesis, exaggerating hyperglycaemia and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations